Large-scale pile tests in clay proceedings of the conference Recent large-scale fully instrumented pile tests in clay held at the Institution of Civil Engineers, London, on 23-24 June 1992 - Clarke, J. (Thomas Telford, 1993)
During the 1980s, research was being carried out to instrument and monitor the piled foundation beneath one leg of the BP Magnus platform in order to determine the actual loads imposed on the piles and seabed by the structural and environmental forces. This volume brings together the findings and discussions resulting from this research.